A Correlational Study of Digital Literacy Comprehension Toward Students' Writing Originality - Nur Muthmainnah (Langkawi: Journal of The Association for Arabic and English, 2019)
This research was aimed to know how far the students’ understanding of digital literacy, to know how high the students’ writing originality, and to know the correlation between students’ understanding of digital literacy and students’ writing originality. Digital literacy is someone’s capability to use the digital device, receive, communicate process, evaluate, and share the information cognitively and technically. Originality is emphasized in writing because it is used as the measurement of the writers’ idea and creativity in writing. This research used correlational study to check the correlation between variable. The population of this research was the 2015th generation of English Education Department Students of IAIN Salatiga. It used cluster random sampling to decide the sample of this research. Class A was used as the sample of the research that consisted of 32 students. The data that was collected was analyzed using SPSS 20. Based on the data analysis, it resulted that r(count) 0.83 > r (table) 0.349. From the result, it can be concluded that there was positive perfect correlation between digital literacy understandings with student’s writing originality